A New Proposed Method to Estimate Attenuation Based on Shift Frequency Method - Hermana, Maman (2010)
This paper presents the improvement of quality factor (Q) estimation using shift frequency method. A new method was developed based on two previous method; Peak Frequency Shift (PFS) and Centroid Frequency Shift (CFS) methods. The new method has been tested to gauge its performance using three different scenarios; Q variation, travel time variation and Signal to Noise (SNR) variation. The test was performed using Ricker wavelet with noise random included. Based on the result obtained, it can be concluded that the new method is able to improve Q estimation using shift frequency method. these method can also be implemented in low and high condition of Q, near and far wavelet target, and in low and high SNR condition of seismic data. The limitation in the PFS and CFS method can be reduced by this method.